PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN TALAOK BAYANG KABUPATEN PESISIR SELATAN - Putri, Novia Isnanni (STKIP PGRI Sumbar, 2014)
This research is motivated by the studentâs understanding on mathematics conpent that still low and students on interest in learning mathematics. This research was aimed at revealing whether the use of Student Teams Achievement Division (STAD) models could give a better effect on the studentâ understanding on mathematics concept than the conventional one in class VIII MTsN Talaok Bayang Kabupaten Pesisir Selatan. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in studentsâ understanding on mathematics concept. Based on the result of data analysis, it was revealed that the sample was distributed normally and had homogeny variant. Hypothesis test results obtained was bigget than indicating that the hypotesis was accepted. So, it was concluded that the application of Student Teams Achievement Division (STAD) models could improve the studentsâ understanding on mathematics concept, and better than the conventional one.